Site-directed mutagenesis on alkaline phosphatasefrom pseudomonas aeruginosapao1 for enhanced activity - UMA SELVARAJ; THIRUMALAI MUTHUKUMARESAN; GAYATHRI VIJAYENDRAN; SENTHIL KUMAR DEVAN; P. VENU-BABU; RICHARD THILAGARAJ WILSON (International Journal of Pharma and Bio Sciences, 2016)
Alkaline phosphatase (ALP) is a hydrolase enzyme known for removing phosphate groups from mono and di-esters and widely used in bioremediation of heavy metals. For effective bioremediation higher turnover rate is required so that the product inorganic phosphate precipitates metals more rapidly. In this paper, the phoA gene from Pseudomonas aeruginosa PAO1 was cloned, over-expressed in E.coli BL21 (DE3) and further purified and characterized. The molecular mass of recombinant enzyme was determined on SDS-PAGE and was found to be 52 kDa. Mutations were performed at the active site residues of the enzyme. Maximum catalytic activity for wild-type enzyme was observed at 45-50°C, pH 8.0 with Km of 75 µM and kcat 113 s-1 on the substrate p-nitrophenol phosphate. Interestingly, the H412R mutant showed 8-fold increase in activity and 6-fold increase in kcat/Km in the presence of 1 mM cobalt. This enhanced enzyme activity after mutation proves effective bioremediation results.